2019
DOI: 10.5830/cvja-2019-012
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling in atrial fibrillation: the impact of amiodarone

Abstract: Atrial fibrillation (AF) is a common heart rhythm disorder with a prevalence of up to 2.9% in the general population. Its mechanism involves a particular electrophysiological profile as well as structural and biohumoral changes that are often irreversible. With the recent advances in pharmacology, amiodarone remains the cornerstone for the treatment of AF. Although it is one of the most controversial anti-arrhythmic agents due to the multitude of side effects, it is further recognised as the most effective dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“… 6 At three months following surgery, the ablation line can scar and form an absolute barrier, which can interrupt the feedback pathway, reduce the AF recurrence rate, and increase the conversion rate to sinus rhythm. 7 Studies have found that postoperative amiodarone for at least three months can impact on the rhythm instability caused by the postoperative inflammation and thereby reduce the risk of AF recurrence; 8 (2) it could be inferred from Table 6 that in the early postoperative period, the LAD was significantly reduced in both groups of patients compared with pre-operation data. The LAD further reduced during the midterm postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“… 6 At three months following surgery, the ablation line can scar and form an absolute barrier, which can interrupt the feedback pathway, reduce the AF recurrence rate, and increase the conversion rate to sinus rhythm. 7 Studies have found that postoperative amiodarone for at least three months can impact on the rhythm instability caused by the postoperative inflammation and thereby reduce the risk of AF recurrence; 8 (2) it could be inferred from Table 6 that in the early postoperative period, the LAD was significantly reduced in both groups of patients compared with pre-operation data. The LAD further reduced during the midterm postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In patients in whom sinus rhythm has been restored, the same drugs used for cardioversion may be used to prevent arrhythmia relapses. Among these drugs, amiodarone has been shown to be the most effective antiarrhythmic, though not without long term side effects [16].…”
Section: Atrial Fibrillation (Fa) Cardioversion and Anticoagulationmentioning
confidence: 99%
“…As more findings emerge from clinical studies and real-world evidence, the use of NOACs is becoming increasingly varied, replacing VKAs therapy in many contexts as a safe, reliable and effective therapeutic approach [9,12,16,17,18,21,43]. However, VKAs still play an important role in countless contexts, including situations where NOACs are contraindicated [36].…”
Section: Novel Oral Anticoagulants (Noacs): a Future Already Presentmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia [1][2][3][4][5]. With increasing life expectancy, the incidence and prevalence of AF continue to rise with an estimated worldwide prevalence of 46.3 million.…”
Section: Introductionmentioning
confidence: 99%
“…Rhythm control, which involves antiarrhythmic drugs (AADs), cardioversion (chemical or electrical), or ablation to maintain sinus rhythm (SR), is considered to be a second-line treatment for AF. When rhythm control is chosen, catheter ablation (CA) for AF is considered as a second-line treatment after failure of at least one AAD or intolerance [5][6][7]. Regardless of which approach is pursued, both require risk factors and stroke risk reduction evaluation.…”
Section: Introductionmentioning
confidence: 99%